Vasculogenic mimicry in malignant ovarian tumours - Czekierdowski, Artur; Czekierdowska, Sylwia; Daniłoś, Jarosław (Menopause Review/Przegląd Menopauzalny, 2011)
Introduction : Neoplastic cells of various malignant tumours may induce formation of “vascular channels” which are not lined with endothelium. This phenomenon has been called “vasculogenic mimicry”. Objectives : To assess the frequency of vasculogenic mimicry in primary and metastatic malignant ovarian masses in women and to compare it with microvascular density of the most vascularized parts of these tumours. Material and methods : Microvessel density (MVD) and PAS-positive structures representing “vascular channels” were assessed with the use of immunohistochemistry in a group of 66 women operated on because of malignant ovarian tumours. CD-34 antigen staining was used for MVD assessment and PAS-positive structures were identified with modified Schiff’s reaction. Results : Mean age of the study group was 53.9 ±11.7 years (median 53 years, range: 23 to 86 years) and 37 women (56.1%) were postmenopausal. There were 37 primary invasive ovarian cancers, 9 cancers of borderline malignancy, 10 tumours were metastatic to the ovary and 3 tumours were of non-epithelial origin (two folliculomas and one dysgerminoma). No PAS-positive structures were found in benign (n = 6) or in borderline tumours. Vasculogenic mimicry was found in 47% of primary malignant cancers, 50% of metastatic masses and 100% of non-epithelial malignant tumours. PAS-positive channels were most frequently found in high grade (G2 and G3) tumours and in advanced clinical stage cancers (FIGO stage III). Tumours with low MVD had vasculogenic channels present in 9 cases and absent in 7 cases. Ovarian malignant tumours with high MVD (> 39 microvessels per HPF) more frequently did not have vascular mimicry present (10 cases with PAS– and 5 cases PAS+). Interestingly, in the vicinity of spots with positive PAS reaction there were only a few CD-34 positive structures identified. Conclusion : Vasculogenic mimicry is a phenomenon that relatively frequently accompanies malignant ovarian neoplasms and can be used as a parameter characterizing the development of alternative vascular-like structure formation in these tumours.